2022
DOI: 10.3389/fcvm.2022.935313
|View full text |Cite
|
Sign up to set email alerts
|

Novel classification for simple peripheral arteriovenous malformations based on anatomic localization: Prevalence data from the tertiary referral center in China

Abstract: BackgroundIn absence of the large-sample study of simple peripheral arteriovenous malfomations (pAVM), we aimed to perform the epidemiological analysis of over 1,000 simple pAVM patients from our center in the past 5 years, and establish a novel classification based on the anatomical localization of the primary lesion.ResultsBetween March 27, 2016, and March 31, 2021, Chinese patients who were diagnosed with simple pAVM were taken into account. Those who suffered from simple arteriovenous malformations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Peripheral AVMs are complex lesions and can be very aggressive locally. They can cross tissue boundaries and even penetrate cortical bone [ 1 ]. Endovascular embolization is particularly effective when treating peripheral AVMs, especially when done using the guidance of the Yakes classification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peripheral AVMs are complex lesions and can be very aggressive locally. They can cross tissue boundaries and even penetrate cortical bone [ 1 ]. Endovascular embolization is particularly effective when treating peripheral AVMs, especially when done using the guidance of the Yakes classification.…”
Section: Discussionmentioning
confidence: 99%
“…Arteriovenous malformations (AVMs) are congenital diseases that usually appear in an insidious form at birth and are easily overlooked during childhood [ 1 ]. Several factors, including trauma, infection, and hormonal changes, lead to the expansion and deterioration of the AVMs lesions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 Because our patient remained asymptomatic, conservative treatment with annual follow-up visits and imaging surveillance was offered based on the current literature. 33 If AVMs progress to become symptomatic and disabling, endovascular embolization or surgical resection could be considered. Until further research is reported, we suggest conservative therapy, including compression and elevation, for asymptomatic patients with AVMs, reserving endovascular or surgical intervention for patients with severe symptoms affecting their daily living activities.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Moreover, when patients with head and neck AVMs turn their heads toward the healthy side, external jugular vein dilatation can be observed on the affected side. 10 Other indicators of patients with AVMs include tortuous and dilated outflow veins, as well as relatively typical local manifestations upon physical examination, including bleeding, ulcers, and infections caused by skin and mucosal ischemia, particularly in patients with acral AVMs. 13 In the later stages of this disease, patients may exhibit decompensated presentations, such as congestive heart failure involving palpitations, shortness of breath, and chest tightness symptoms, owing to long-term increased venous return.…”
Section: Clinical Presentation and Stagingmentioning
confidence: 99%